World Religions and Their Missions - Kluj, Wojciech (Annales Missiologici Posnanienses, 2023)
Recenzja książki: World Religions and Their Missions, ed. by Aaron J. Ghiloni, New York–Bern–Frankfurt–Berlin–Brussels–Vienna–Oxford–Warsaw, Peter Lang, 2015, s. 349.